Sulfur Poisoning and Performance Recovery of SOFC Air Electrodes - Hong, Junsung; Anisur, M. R.; Heo, Su Jeong; Dubey, Pawan Kumar; Singh, Prabhakar (Frontiers in Energy Research, 2021)
The sulfur poisoning and performance recovery of the state-of-the-art SOFC cathodes, (La0.80Sr0.20)0.95MnO3±δ (LSM) and (La0.60Sr0.40)0.95Co0.20Fe0.80O3-δ (LSCF), have been studied. Electrochemical impedance spectroscopy measurements of LSCF|GDC and LSM|YSZ half-cells are carried out in alternating atmospheres of air and SO2–air at 700 °C for hundreds of hours. In the presence of SO2, the electrochemical performance of both the cells decays with ohmic and non-ohmic losses, owing to the absorption and chemical interaction of SO2 with the electrodes. In LSCF, the SrO segregated on the surface tends to absorb and react with SO2, forming SrSO4 followed by exsolution of Co-Fe. As for LSM, SO2 is absorbed onto Sr-rich areas of LSM, including the active reaction sites near the TPBs, leading to Sr exsolution and SrSO4 formation, leaving Sr-deficient LSM. During subsequent exposure to air, the performance of the sulfur-contaminated LSM is almost restored. The LSM particles, exposed to alternating atmospheres of air and SO2-air during the electrochemical tests, show a relatively clean surface with sparsely distributed SrSO4 particles, indicating high stability against sulfur poisoning. It is suggested that loosely adsorbed SO2 at the TPBs is readily swept away by the SO2-free air flow, recovering its ORR activity, whereas the Sr-deficient LSM due to Sr-exsolution stays modified, contributing to the incomplete performance restoration. Unlike the case of LSM, the performance of the sulfur-poisoned LSCF only partially recovers during the subsequent exposure to air. Correspondingly, the LSCF particles have a modified morphology covered with numerous nanoparticles, mostly SrSO4, showing the irreversible aspect of the sulfur poisoning. The morphology modification is not concentrated near the electrode/electrolyte interface but over the entire cathode, indicating that the degree of recovery from sulfur poisoning is closely related to the presence of SrO and chemical activity of Sr in the electrodes at the solid-gas interface. Our results also show the potential application of LSM for a sulfur sensor available in high-temperature harsh conditions.